ETHNOBOTANICAL ANALYSIS OF PHYTONYMS AND PLANT-RELATED GLOSSES MENTIONED IN BUJANGGA MANIK, A PRE-ISLAMIC SUNDANESE TEXT (15TH CENTURY JAVA, INDONESIA) - Mulyanto, Dede; Iskandar, Budiawati Supangkat; Iskandar, Johan; Indrawardana, Ira; Aufa, Ari Abi (REINWARDTIA, 2023)
This study aimed to identify and analyze ethnobotanical data on phytonym, utilization, and cultural value of plants mentioned in an Old Sundanese text. Since plants are mentioned with their vernacular names, identification was based on an exhaustive bibliographical search of the respective scientific name. A comprehensive investigation led to the identification of a total of 85 Old Sundanese phytonyms, which represented vernacular names for 79 distinct plant species. Furthermore, by considering the number of identified species from the plant-related glosses, 93 species belonging to 57 genera and 44 plant families were registered. Among these plant families, Arecaceae (12 species), Poaceae (nine species), and Fabaceae (six species) exhibited the highest number of identified species. In addition to the phytonyms, 36 phytotoponyms, which utilize vernacular phytonyms to designate settlements, hermitages, ports, mountains, and rivers were identified. It was worth noting that the majority of the plants associated with these phytotoponyms were indigenous. Meanwhile, only 13 species were traced back to the pre-Columbian exchange period during the Austronesian migration and the Indianization-Sinicization era in IndoMalayan history. The result showed that the predominantly mentioned utilization included beverage production, textile manufacturing, vessel craftsmanship, betel quid preparation, perfume creation, and incense production. Among the identified species, Areca catechu emerges as the most frequently mentioned in the text, along with Graptophyllum pictum and Cordyline fruticosa, which were also considered as possessing profound spiritual value due to association with heavenly realms. Furthermore, the text highlighted that the production of plant-based fragrance products, also referenced in the celestial domain, held significant prominence in global trade during the 15th century